ICT Based Instructional Design for Inquiry Based Learning and Project Based Learning - Khaerotun Nisa Nisaaaaa; Syifa Amelia Permata; Syifa Ulfiyana Ramadhanti; Riris Eka Setiani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The rapid development of Information and Communication Technology (ICT) has brought significant changes to education, particularly in designing innovative, student-centered learning. This article aims to examine the concept of ICT-based instructional design and its integration with Inquiry Learning and Project-Based Learning (PjBL) in Islamic Religious Education (PAI). The study employed a library research approach by reviewing literature retrieved from Google Scholar, Garuda, and SINTA databases using the keywords ICT-based instructional design, Inquiry Learning, Project-Based Learning, and Islamic Religious Education, with publications limited to the past ten years. The data were analyzed thematically following the Miles and Huberman framework, including data reduction, data display, and conclusion drawing. The findings indicate that these three components are integrated into a coherent instructional design framework. ICT initially functions as a medium for inquiry by enabling students to explore Islamic texts, examine Islamic history, and analyze digital Islamic resources. The outcomes of the inquiry process then serve as the foundation for developing digital religious products within the Project-Based Learning framework, such as infographics on Islamic moral values, videos of community-based religious projects, and multimedia presentations on Islamic Religious Education topics. Thus, ICT serves not merely as a supporting tool but as a bridge connecting critical thinking fostered through inquiry with creative project-based activities, making Islamic Religious Education more interactive, meaningful, and relevant to the demands of twenty-first-century learning.